(untitled) (Swiss Medical Weekly, 2026)
PURPOSE: Immune checkpoint inhibitors have revolutionised the management of non-small cell lung cancer (NSCLC) without oncogenic addictions and have improved its prognosis. A manifestation of acquired resistance to immunotherapy, which is typically seen in a restricted number of lesions and metastatic locations (oligoprogression), has been reported. In cases of oligoprogressive disease, local ablative therapies may represent the main therapeutic approaches, and their significance is further amplified for patients with metastatic NSCLC undergoing immunotherapy. METHODS: This monocentric retrospective study included 49 patients with metastatic NSCLC treated with immunotherapy, either as a standalone treatment or in combination with chemotherapy. The patients also underwent local ablative therapy in the context of oligoprogression. Clinical and oncological characteristics were assessed, along with overall survival and progression-free survival. RESULTS: The clinical and oncological characteristics were generally consistent with those expected in the general population of patients with metastatic NSCLC. A median overall survival of 28 months (95% CI: 17.4%–33%), measured from the initiation of local treatment, was reported. The 5-year overall survival rate was 12.36%, and the median progression-free survival was 7.56 months (95% CI: 6.01%–11%). The addition of local ablative therapy to immunotherapy was not associated with increased toxicity. CONCLUSION: The addition of local ablative therapy in cases of oligoprogression as part of the treatment of metastatic NSCLC treated with immunotherapy alone or in combination with chemotherapy appears to be a therapeutic strategy for slowing disease progression.